Uji Efektivitas Serbuk Daun Kipait (Tithonia difersivolia) Terhadap Serangan Nematoda Puru Akar (Meloidogyne Spp) pada Tanaman Tomat - Rahmat Wardani Yansyah; Elly Liestiany; Dewi Fitriyanti (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
The tomato plant (Lycopersicum esculentum Mill.) is a horticultural plant that is popular with the public because it has good nutritional content, including vitamin A, vitamin B and vitamin C, which have quite high levels which are good for the body to consume. One of the pests that affects tomato plant production, both quality and quantity, is the attack by root knot nematodes (NPA), namely Meloidogyne spp. This research aims to determine the ability of kipahit leaf powder in several doses to suppress attacks by root knot nematodes (Meloidogyne spp.) on tomato plants (Lycopersicum esculentum Mill.). This research was designed using a one-factor Completely Randomized Design (CRD). The factors tested were the administration of kipahit leaf powder at doses of 25 grams, 50 grams, 75 grams and 100 grams with the control treatment not being given kipahit leaf powder as a comparison. This study had 5 treatments and 4 replications. The research results showed that giving 50 grams of kipahit leaf powder was able to reduce the intensity of root knot attacks and could reduce the nematode population around the roots of tomato plants. and had a significant effect on plant height at 46 and 60 days after transplanting.